Audit Kepatuhan Dan Kinerja Perusahaan: Sebuah Studi Literatur - Konstantinus Pati Sanga; Thadeus Fransesco Quelmo Patty; Maria Viviana Nurak Lewar (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
Compliance auditing is an internal activity required by organizations to provide objective assurance and consultation, improve operations, and add value. This article discusses the concept, objectives, stages of a compliance audit, as well as its relationship to company performance. Compliance risk is a major concern, especially with regard to regulatory changes that can lead to compliance errors. Compliance audits play an important role in evaluating and ensuring a company's compliance with applicable regulations, identifying risks, and providing recommendations for improvement. The research method uses literature study by collecting data from various literature sources. The conclusion emphasizes the importance of compliance audits in reducing legal risks, identifying improvement opportunities, and enhancing security measures, as well as understanding their relationship with company performance to support long-term growth and reputation.